2013
DOI: 10.1096/fj.13-236570
|View full text |Cite
|
Sign up to set email alerts
|

Generation of an efficiently secreted, cell penetrating NF‐κB inhibitor

Abstract: Gene therapy is a powerful approach to treat disease locally. However, if the therapeutic target is intracellular, the therapeutic will be effective only in the cells where the therapeutic gene is delivered. We have engineered a fusion protein containing an intracellular inhibitor of the transcription factor NF-κB pathway that can be effectively secreted from producing cells. This fusion protein is cleaved extracellularly by metalloproteinases allowing release of a protein transduction domain (PTD) linked to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…The delivery of bioactive molecules like enzymes, hormones, nucleic acids and transcription factors in a targeted manner remains a challenge in the development of novel therapies. In many cases, it is effective only in the cells where the therapeutic agent is delivered [ 152 ]. As human tissues are transparent to magnetic fields, the encapsulation of magnetic nanoparticles enables magnetic navigation with the external magnetic fields and accumulation of the carriers in the desired site of action [ 153 , 154 , 155 ] due to the increased microcapsule concentration at the magnetic site [ 156 ].…”
Section: Applications Of Oil-core Nanocapsulesmentioning
confidence: 99%
“…The delivery of bioactive molecules like enzymes, hormones, nucleic acids and transcription factors in a targeted manner remains a challenge in the development of novel therapies. In many cases, it is effective only in the cells where the therapeutic agent is delivered [ 152 ]. As human tissues are transparent to magnetic fields, the encapsulation of magnetic nanoparticles enables magnetic navigation with the external magnetic fields and accumulation of the carriers in the desired site of action [ 153 , 154 , 155 ] due to the increased microcapsule concentration at the magnetic site [ 156 ].…”
Section: Applications Of Oil-core Nanocapsulesmentioning
confidence: 99%
“…Also, in a cross-sectional study, premenopausal women with the BAt haplotype had significantly lower levels of calcium absorption than women with the baT haplotype [9]. In addition, in a separate pilot analysis of twenty-seven women who were randomly assigned in a double blind manner to 2500 IU/d or 400 IU/d supplemental vitamin D 3 intake, the FCA response to high vitamin D intake was significantly attenuated in women with the BB compared to bb genotype [31]. These data indicate that VDR polymorphisms exhibit a modest effect on calcium absorption even under stable conditions, suggesting that weight loss is not the only contributing factor to calcium absorption.…”
Section: Discussionmentioning
confidence: 99%
“…This could explain the absence of recombinant protein in the culture medium although it is being expressed at gene level. Contrary, Koutsokeras et al (2014) reported that PTD fused to protein of interest is the culprit that inhibit the secretion of the protein itself.…”
Section: -Azacytidine (5-azac) Treatment Was Able To Restore the Expmentioning
confidence: 98%